Dynamics between Actors and Interest Groups in an Environmental Politics Perspective: Case Study of Food Estate Development in Kalimantan - Gaudart, Aqil Rizaldi; Pasha, Julian Aldrin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is aimed at understanding the dynamics between actors in the national food barn project during the Joko Widodo administration in Central Kalimantan for the 2020-2023 period. Through qualitative research, the research focus was carried out by analyzing several indicators using actor and interest group theory from a political ecology perspective. This research reveals that the food estate policy carried out by the government in Central Kalimantan was carried out without clear regulations and was carried out haphazardly, the actors and interest groups involved, namely the government, the private sector, civil society alliances. Based on field findings, there is a relationship between the private sector and political elites who occupy positions in government. . This research reveals the pattern of relations between government and the private sector in implementing food estate policy and also the main issues at play. Meanwhile, civil society alliance groups act as opposing groups that play an important role as critics of this policy. There are two issues on the main agenda which are strong reasons for this group to have a different attitude to the government